2020
DOI: 10.3389/fonc.2020.00345
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Institutional Analysis of Synchronous Prostate and Rectosigmoid Cancers

Abstract: Purpose: To perform a multi-institutional analysis of patients with synchronous prostate and rectosigmoid cancers. Materials and Methods: A retrospective review of Duke University and Durham Veterans Affairs Medical Center records was performed for men with both prostate and rectosigmoid adenocarcinomas from 1988 to 2017. Synchronous presentation was defined as symptoms, diagnosis, or treatment of both cancers within 12 months of each other. The primary study endpoint was overall survival. Univariate and multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…The incidence of D/MPMTs with prostate and colorectal origin varies considerably depending on the inclusion criteria, the size and characteristics of the cohort, the involved anatomical region of the large bowel, and the length of the follow-up ( Table 3 ) ( Jacobs et al, 2020 ; Kavanagh et al, 2012 ; L. Liu et al, 2011 ; Sturludóttir et al, 2015 ). Compared with Sturludóttir et al, who analyzed the association between PC and rectal cancer over a period of 16 years, Jacobs et al reported a twofold higher incidence for synchronous PC and rectosigmoid cancer over a period of 20 years ( Jacobs et al, 2020 ; Sturludóttir et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The incidence of D/MPMTs with prostate and colorectal origin varies considerably depending on the inclusion criteria, the size and characteristics of the cohort, the involved anatomical region of the large bowel, and the length of the follow-up ( Table 3 ) ( Jacobs et al, 2020 ; Kavanagh et al, 2012 ; L. Liu et al, 2011 ; Sturludóttir et al, 2015 ). Compared with Sturludóttir et al, who analyzed the association between PC and rectal cancer over a period of 16 years, Jacobs et al reported a twofold higher incidence for synchronous PC and rectosigmoid cancer over a period of 20 years ( Jacobs et al, 2020 ; Sturludóttir et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of D/MPMTs with prostate and colorectal origin varies considerably depending on the inclusion criteria, the size and characteristics of the cohort, the involved anatomical region of the large bowel, and the length of the follow-up ( Table 3 ) ( Jacobs et al, 2020 ; Kavanagh et al, 2012 ; L. Liu et al, 2011 ; Sturludóttir et al, 2015 ). Compared with Sturludóttir et al, who analyzed the association between PC and rectal cancer over a period of 16 years, Jacobs et al reported a twofold higher incidence for synchronous PC and rectosigmoid cancer over a period of 20 years ( Jacobs et al, 2020 ; Sturludóttir et al, 2015 ). Another study from Czech Republic showed that 2.3% of patients diagnosed with CRC between 2003 and 2013 and followed until 2018 developed PC ( Halamkova et al, 2021 ), in line with a Swedish study that has shown that 1.9% of those over 72,000 patients have associated colon cancer and PC ( Van Hemelrijck et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations